Determination of Tolterodine Via Ion Pair Complex Using Spectrophotometric Method in Pharmaceutical Formulation - Ibrahim, Munjed M.; Alarjah, Mohammed (Current Pharmaceutical Analysis, 2018)
Background: Tolterodine was quantitatively determined using variable analytical methods including; spectrophotometric and chromatographic methods. Spectrophotometric methods are usually fast, easy to handle, cost effective and very reliable for the routine assay during in process quality control procedures. Eosin Y has been used to determine several basic compounds through the formation of colored complexes. In this research work, spectrophotometric method is developed to determine Tolterodine in bulk and in tablet via ion pair complex with Eosin as complexing agent. Methods: The method developed in this work was based on the formation of a colored binary complex between the tertiary amine group in (TOL) molecule and the hydroxyl group in Eosin Y molecule. The absorbance of the chloroform extractable complex was measured at 530 nm using spectrophotometric technique. Result: The method obeyed Beers Lambert law and the linearity range was 18.6 -58.2 μg mL-1. The calibration curve equation is Y=9.28X + 0.07 with a linear regression of 0.992. The method was applied for the assay of (TOL) in commercially available tablets. Conclusion: Sensitive, specific, accurate and cost effective analytical method was developed in this work. It was found that the method could be used for a quick assay of the Tolterodine tartrate in bulk and in pharmaceutical dosage form for research and quality control purposes.
Keywords: tolterodine